Impact of a multidisciplinary team meeting on patient-reported outcomes at 2 years after lumbar surgery: A prospective comparative exploratory study. Issue 47 (25th November 2022) - Troussier, Sébastien; Ferrero, Emmanuelle; Lefèvre-Colau, Marie-Martine; Feydy, Antoine; Guigui, Pierre; Rannou, François; Nguyen, Christelle
Abstract : Failed back surgery syndrome is a challenge. We hypothesized that a multidisciplinary team meeting (MTM) may be useful to select patients who are the most likely to benefit from lumbar surgery. We conducted an observational, prospective, comparative, exploratory study. We aimed to compare core clinical patient-reported outcomes at 2 years after lumbar surgery between patients who attended a MTM and those who did not. Patients who underwent lumbar surgery for a degenerative disease, in a single academic orthopedic department, between January and September 2018, were consecutively screened. Eligible patients were surveyed between April and June 2020. Patient-reported outcomes included lumbar and radicular pain, spine-specific activity limitations and health-related quality of life assessed via self-administered questionnaires. Outcomes were compared between respondents who attended the MTM and those who did not. Overall, 211 patients underwent lumbar surgery, 108 were eligible and 44 included: 11 attended the MTM and 33 did not. Mean participants' age was 57.4 (15.4) years, symptom duration was 14.8 (15.3) months, lumbar pain was 51.3 (18.2) and radicular pain was 53.4 (18.6). At 2 years, we found no evidence that lumbar and radicular pain, activity limitations and health-related quality of life differed between the 2 groups. The decrease was −26.8 (41.1) versus −20.8 (30.4) in lumbar pain and −25.5 (43.0) versus −19.5 (27.5) in radicular pain, in participants who attended the MTM versus those who did not, respectively. We found no evidence that core clinical patient-reported outcomes at 2 years after lumbar surgery differed between participants who attended the MTM and those who did not. However, the exploratory design of our study does not allow concluding that MTMs do not have an impact.